Confirming non-endemicity of podoconiosis in Guatemala and in Idukki District in Kerala (India): a comparison of two approaches potentially suitable for other neglected tropical diseases - Simpson, Hope; Trueba, Mei; Mendizábal-Cabrera, Renata; George, Sobha; Tomy, Chitra; Sasi, Silpa T.; Kartal, Aran; Deribe, Kebede; Panicker, Kottarathil Narayanpillai Parameswara; Davey, Gail (BMC Global and Public Health, 2024)
Podoconiosis is an underreported lymphoedema whose distribution is uncertain at global level and within endemic countries. Previous work has identified countries with historical evidence of podoconiosis, but which do not currently report cases. Podoconiosis may persist in these countries or have been eliminated due to socioeconomic development. Here we describe two different approaches used to clarify podoconiosis endemicity status in Guatemala and in Idukki District (Kerala State, India).